Understanding the role of regulatory flexibility and context sensitivity in preventing burnout in a palliative home care team - Lenzo, Vittorio (PLoS One, 2020)
Although burnout syndrome has been investigated in depth, studies specifically focused on palliative home care are still limited. Moreover, there is still a lack of evidence regarding the interplay between emotional flexibility and sensitivity to context in preventing burnout in home care settings. For these reasons, the aims of this study were to examine burnout symptoms among practitioners specializing in palliative home care and to investigate the role of regulatory flexibility and sensitivity to context in understanding burnout. An exploratory cross-sectional design was adopted. A convenience sample (n = 65) of Italian specialist palliative care practitioners participated in this study. Participants were recruited between February and April 2019 from two palliative home care services that predominantly cared for end-of-life cancer patients. The Italian version of the Maslach Burnout Inventory (MBI), the Flexible Regulation of Emotional Expression (FREE) scale (a measure of emotional flexibility), and the Context Sensitivity Index (CSI) (a measure of sensitivity to context) were administered. Analyses of variance were conducted using the three MBI factors as dependent variables and profession as an independent variable. Subsequently, three identical analyses of covariance were conducted with age, work experience, flexibility and sensitivity to context as covariates. The results showed a low burnout risk for all three of the MBI factors, and there were no gender differences. An ANOVA revealed a significant effect of profession type and age on the emotional exhaustion factor of the MBI, and an ANCOVA indicated that these effects persisted after covariates were accounted for. The results also showed a significant effect of the FREE score on emotional exhaustion. These findings can help explain the differential contributions of profession type and age to the burnout symptoms investigated. In addition, the emotional flexibility component, as an aspect of resilience, represents a significant and specific factor of emotional exhaustion. Interventions to prevent burnout must consider these relationships.